2003
DOI: 10.1577/1548-8454(2003)065<0021:eospag>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sodium Percarbonate and Garlic Extract onIchthyophthirius multifiliisTheronts and Tomocysts: In Vitro Experiments

Abstract: White spot disease, which is caused by infections of Ichthyophthirius multifiliis, has a severe impact on productivity in freshwater aquaculture. These infections were previously treated effectively with malachite green, a compound that is now banned on fish farms due to its carcinogenicity. However, aquaculturists need alternative substances to control the disease. Therefore, comparative laboratory tests (in vitro exposure) were performed to elucidate the effects on the infective theront stage and the tomocys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
100
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 12 publications
(13 reference statements)
5
100
0
Order By: Relevance
“…In our study, tomonts were obtained according to the method as described above, but tomont survivals (in the control of the four experiments) were only approximately 90%. The result was close to that of Buchmann et al (2003). This demonstrated that about 10% of the parasites appeared dead or had abnormal reproduction in the incubation.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In our study, tomonts were obtained according to the method as described above, but tomont survivals (in the control of the four experiments) were only approximately 90%. The result was close to that of Buchmann et al (2003). This demonstrated that about 10% of the parasites appeared dead or had abnormal reproduction in the incubation.…”
Section: Discussionsupporting
confidence: 77%
“…These data indicated that tomonts were less susceptible to potassium ferrate(VI) than theronts. Buchmann et al (2003) findings suggested that the tomonts resisted some substances better than the theronts. Combined with the results of Straus and Meinelt (2009) and Meinelt et al (2009), it is shown that peracetic acid (PAA) leads to more toxicity to theronts than tomonts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formerly, ichthyophthiriasis was treated using malachite green and mixtures of malachite green and formalin by immersion with a good deal of success (Leteux and Meyer 1972;Wahli et al 1993;Dickerson and Dawe 1995;Buchmann et al 2003). However, the use of malachite green for the treatment of disease has been no longer permitted by some government agencies, such as the Food and Drug Administration of the USA, due to its potential carcinogenic and teratogenic properties (Alderman 1985;Srivastava et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This organic (triphenylmethane) dye was favoured for the control of I. multifiliis infections because of its high efficacy against both the free-swimming stages (protomonts and theronts) of the parasite and the feeding parasite stage (trophont) within the fish's epithelium (Wahli et al 1993;Tieman and Goodwin, 2001;Buchmann et al 2003). MG and its derivatives (mainly leucomalachite) also display well-documented ecotoxicological effects including cytotoxicity, carcinogenicity, mutagenicity, induction of chromosomal fractures, teratogenicity and respiratory toxicity (Culp and Beland, 1996;Srivastava et al 2004).…”
Section: Introductionmentioning
confidence: 99%